Study of thread tension settings for shirt manufacture using an instrumented lockstich sewing machine - Mellero, Patrícia (2017)
Proceedings of the 7th International Conference on Mechanics and Materials in Design, Albufeira/Portugal 11-15 June 2017. Editors J.F. Silva Gomes and S.A. Meguid. Publ. INEGI/FEUP (2017)